A CLOSER LOOK AT THE ELT REAL PRACTICE UTILIZING E-MAGAZINE IN AN INDONESIAN UNIVERSITY - Anisa Putri Cahyani (PRIMACY Journal of English Education and Literacy, 2023)
Authentic material could be promising in providing real use of language materials, one of them is e-magazines. English e-magazines are the teaching media utilized by the teacher (as the subject of this research) in their ELT class that become the focus of this study. Aiming at describing the real practice done by the teacher in order to look closer on how e-magazine presence in class can help ELT teaching learning process, this article presents a case study of an ELT class of 30 students in an Indonesian art university, involving a teacher and several students in the process of data collection through observation, interview, and document study and analyzed by having critical look on the process of real teaching practice. The result shows there are gained benefits related to students’ learning autonomy, with some potentials and challenges related to teaching practices, hoping that ELT teachers could develop their teaching ideas and might consider using e-magazine in their next class meetings.